Challenges in the Preservation of Cultural Heritage Samples through Digital Technology in the Republic of Azerbaijan - Guliyeva, Firangiz; Orujova, Turkan; Rovshan, Gulay (ADA University, 2024)
This thesis is focused on the complex issues connected with preserving Azerbaijan's rich cultural heritage and the promising opportunities in this process, especially the use of digital technology. It thoroughly examines the current state of digital preservation in Azerbaijan. Thus, it reveals the most significant obstacles, such as the lack of funds, the insufficient technological infrastructure, and the shortage of skilled professionals who are able to implement and manage advanced digital solutions. Through the interviews with experts from Azerbaijan's heritage industry, the research shows the change that AI and other digital technologies can bring to the protection and accessibility of cultural artifacts. The comparison of Azerbaijan with neighboring countries such as Georgia, Turkey, and Kazakhstan gives insight into the successful strategies and best practices that can be adopted in Azerbaijan. These countries have successfully used digital technologies in cultural preservation and can serve as a case study for Azerbaijan. The research stresses the government's importance in allocating more funds to the issue, creating specialized training programs, and running public awareness campaigns to build a viable digital preservation framework. The difficulties that Azerbaijan faces can be solved by ensuring the safety and the continuous preservation of its cultural heritage. Thus, the country's people are more connected to their roots and, at the same time, part of the global culture. This thesis suggests a complete analysis and the recommendable solutions for improving Azerbaijan's cultural heritage preservation.
Keywords: Cultural property -- Preservation -- Azerbaijan; Digital preservation -- Azerbaijan; Cultural heritage -- Protection -- Azerbaijan; Azerbaijan -- Cultural policy; Public and International Affairs